New combinations in the genus Goeppertia (Marantaceae) - Braga, João Marcelo Alvarenga (Phytotaxa, 2014)
Calathea basiflora , C. rhizanthoides and C. peregrina were recently described for the Flora of Panama and because the majority of the species of Calathea are now placed in Goeppertia, the combinations for these species are hereby provided.